Estudo da diversidade genética e química e produção do epímero do ácido caurenóico em calos de croton antisyphiliticus mart - Oliveira, Taíce Gonçalves de [UNESP] (2015)
Croton antisyphiliticus Mart. ex M. Arg. is a medicinal plant native of the Cerrado, used in folk medicine for the urogenital tract infections. The aim of this study were to establish callus culture, evaluate the genetic and chemistry variability in natural populations of C. antisyphiliticus using AFLP molecular markers and quantify by HPLC the ent-kaur-16-en-18-oico acid in leaf, root and callus. For callus induction was used stem segments and leaves, inoculated in Murashige and Skoog supplementend with auxin IBA, NAA and 2,4-D. The genetic diversity and chemistry was performed from accesses collected in the states of Minas Gerais, São Paulo and Goiás. The genotyping of individuals was held in 4300 DNA Analyzer equipment LI-Cor®. The highest yield the acid content Kaur-ent-16-en-18-oic acid (38,54) was obtained in the culture medium supplemented with 4 mg/l 2,4-D in the thirty-sixth day. The AFLP molecular marker was efficient to characterize the genetic variability in populations of C. antisyphiliticus. The variability within populations was greater than between them and the value of Fst was 0.3830 showing that the populations are highly structured. The highest percentage of polymorphic loci (92.16%) and the greatest genetic diversity was found in the access of the population of Pratinha. Gene flow was considered restricted (Nm = 1.18) and there was no correlation between genetic and geographic distances. The chemical diversity found among and within populations was related both the genetic factors and environmental, and production of ent-kaur-16-en-18-oic acid by tissue culture was most viable than from plants collected in situ.